TB treatment delay associated with drug resistance and admission at Daru General Hospital in Papua New Guinea - Hapolo, E. (Public Health Action, 2019)
SETTING: Daru General Hospital, Daru Island, Papua New Guinea, where high rates of tuberculosis (TB) have been reported. Prompt diagnosis and effective treatment are needed for improving TB outcomes and to prevent nosocomial transmission. OBJECTIVE: To assess the time to treatment initiation and the risk factors associated with delayed treatment for patients started on TB treatment at Daru General Hospital from January to September 2017. DESIGN: This was a retrospective cohort study that entailed reviewing the records from treatment, admission, discharge and presumptive TB registers. RESULTS: The study included 360 patients on TB treatment. The median time from presentation to treatment initiation was 7 days [IQR 3–11]. Treatment was started <7 days for 215 patients (60%); however, only 16.2% commenced treatment <2 days. Risk factors for delayed treatment were diagnosis of TB as an inpatient (OR 2.67, 95% CI 1.35–5.28, P = 0.005) and having drug-resistant TB (OR 2.65, 95% CI 1.5–4.68. P = 0.001). CONCLUSION: A high proportion of TB patients commenced treatment <7 days. Inpatient status, DR-TB and lack of microbiological confirmation were associated with delays in treatment initiation. We recommend that programmes monitor the time from presentation to treatment initiation, and propose that a period of >3 days from presentation to treatment initiation be considered as delayed treatment initiation.